2007
DOI: 10.1074/jbc.m707622200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Phosphatidylinositol 3-Kinase/Akt/Glycogen Synthase Kinase-3β Signaling Pathway in Recovery from Anthrax Lethal Toxin-induced Cell Cycle Arrest and MEK Cleavage in Macrophages

Abstract: Anthrax lethal toxin (LeTx) is a virulence factor causing immune suppression and toxic shock of Bacillus anthracis infected host. It inhibits cytokine production and cell proliferation/differentiation in various immune cells. This study showed that a brief exposure of LeTx caused a continual MEK1 cleavage and prevented tumor necrosis factor-alpha (TNF) production in response to lipopolysaccharide (LPS) in non-proliferating cells such as human peripheral blood mononuclear cells or mouse primary peritoneal macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 51 publications
(68 reference statements)
5
48
0
Order By: Relevance
“…Response to LPS in LeTx-exposed Murine Macrophages-LeTx suppresses expression of various inflammatory cytokines by inactivating MEKs (3)(4)(5). Consistent with these reports, a sublethal dose of LeTx (100 ng/ml PA and LF, each for 4 h) completely cleaved MEK1 and inhibited expression of pro-IL-1␤ induced by LPS (100 ng/ml) for more than 2 days in RAW264.7 macrophages (Fig.…”
Section: Hdac8 Inhibition Restores the Production Of Pro-il-1␤ Insupporting
confidence: 76%
See 1 more Smart Citation
“…Response to LPS in LeTx-exposed Murine Macrophages-LeTx suppresses expression of various inflammatory cytokines by inactivating MEKs (3)(4)(5). Consistent with these reports, a sublethal dose of LeTx (100 ng/ml PA and LF, each for 4 h) completely cleaved MEK1 and inhibited expression of pro-IL-1␤ induced by LPS (100 ng/ml) for more than 2 days in RAW264.7 macrophages (Fig.…”
Section: Hdac8 Inhibition Restores the Production Of Pro-il-1␤ Insupporting
confidence: 76%
“…The causative agent of anthrax is Bacillus anthracis, and LeTx is a main virulence factor that causes immune paralysis and mortality (1). LeTx is known to cause immune suppression by targeting the MAPK pathway that is involved in many aspects of immune responses (2)(3)(4)(5). It includes two proteins, protective antigen (PA) 2 and lethal factor (LF) (6 -10).…”
mentioning
confidence: 99%
“…Total cell lysate preparation and immunoblotting procedures were performed as previously described (25). Briefly, cells were lysed in ice-cold lysis buffer (20 mM MOPS, 2 mM EGTA, 5 mM EDTA, 1 mM Na 3 VO 4 , 40 mM ␤-glycerophosphate, 30 mM NaF, and 20 mM sodium pyrophosphate (pH 7.2)) containing a protease inhibitor cocktail (Roche).…”
Section: Total Cell Lysate Preparation and Immunoblottingmentioning
confidence: 99%
“…Cells were grown at 37°C in the humidified atmosphere of 5% CO 2 . Human PBMC were isolated from whole blood as previously described (25).…”
Section: Cell Culturementioning
confidence: 99%
“…We determined whether the phosphatidylinositol 3-kinase/PTEN/Akt/GSK3h pathway had a role in the observed PA/LF resistance. It has recently been shown that the activation of Akt causes the inhibition of GSK3h-mediated cyclin D1 degradation and consequential G 0 -G 1 cell cycle arrest (23). This activation is critical for recovery from LeTx-mediated cell cycle arrest and resistance to subsequent toxin challenge in human macrophages (23).…”
Section: Discussionmentioning
confidence: 99%